Integrated cathodic protection (CP) sensor network development of the CP sensor - Wold, K.; Johnsen, R.; Iannuzzi, Mariano; Årtun, L. (2018)
© 2018 by NACE International. This paper describes a new CP monitoring approach to quantify the health of the CP system in real-time with spatial resolution. Spatial resolution is achieved by an integrated sensor network distributed across a Subsea Production System. A set of small sensors capable of monitoring potential and current supply as a function of time are distributed across subsea equipment. Realtime data logging is possible by integrating the sensor network into the electronics of the subsea Production and Control System, which can be used for risk assessment, and actioning from surface equipment or automatically without human intervention. The monitoring device is based on the measurement of the galvanic current and potential (i.e. the polarization of the structure) between a sensing surface of known exposed area connected to i) a sacrificial anode or ii) a component attached to the CP system. The sensing elements constitute the main part of the concept and, thus, their choice requires special materials selection considerations. In this work, four different sensing element materials-namely, 25Cr super duplex stainless steel (UNS S32750), 6Mo austenitic stainless steel (UNS S31254), nickel aluminum bronze (NAB), and Titanium Grade 2 (UNS R50400) - have been tested in natural seawater at 10°C for up to 120 days. To minimize the formation of calcareous deposits on the sensing elements, which alters the current response of the sensors, the connection between the sensing elements and the anode/structure was switched ON and OFF. Different ON/OFF cycles were investigated. The outcome of the test program and the status of the sensor development, including materials selection and calibration curves, is presented.